The effects of immigration and skills on urban income inequality in New Zealand: two decomposition approaches - Omoniyi B Alimi; David C Maré; Jacques Poot (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
Income inequality in New Zealand has been a growing concern since the 1980s. Inequality did indeed increase since then, particularly in metropolitan areas. At the same time, policies of encouraging permanent and temporary immigration led to the foreign born accounting for a growing share of the population, again particularly in metropolitan areas. This paper investigates the impact of immigration, by skill level and length of stay, on the distribution of income in urban areas. We apply, and reconcile, sub-group and Shapley-value regression decomposition methodologies to census microdata. We find that over the 1986-2013 period the inequality-increasing effects of immigration size and composition are together somewhat larger than the inequality-reducing effects of changes in the size and composition of the New Zealand born population. Additionally, changes in the skill distribution of the work force in New Zealand have been very important for changes in the distribution of income, regardless of migration status. While the sub-group decomposition of inequality change yields qualitatively similar contributions to 1986-2013 change as regression decomposition, the numerical effects differ markedly between the two methodologies.
Keywords: 330; Decomposition; Immigration; Income inequality; Shapley-value; Urban areas; New Zealand